2022
DOI: 10.3389/fpubh.2022.808626
|View full text |Cite
|
Sign up to set email alerts
|

Spoligotyping of Clinical Isolates of Mycobacterium tuberculosis Complex Species in the Oromia Region of Ethiopia

Abstract: BackgroundTuberculosis (TB) is a leading cause of morbidity and mortality in Ethiopia. Investigation of the Mycobacterium tuberculosis complex (MTBC) species circulating in the Ethiopian population would contribute to the efforts made to control TB in the country. Therefore, this study was conducted to investigate the MTBC species and spoligo patterns in the Oromia region (central) of Ethiopia.MethodsA cross-sectional study design was used to recruit 450 smear positive pulmonary TB (PTB) cases from the Oromia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Consistent with earlier research conducted in various regions of Ethiopia [ 25 , [31] , [32] , [33] , [34] , [35] , 62 , 66 , 67 ], the SIT149/T3-ETH sub-lineage, which has been found to be more likely in a cluster [ 13 , 20 , 65 ], was the most common in our study, followed by the SIT52/T2 spoligotype. In the current study region, SIT149/T3-ETH sublineage [ 39 ] was reported as a predominant TB strain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with earlier research conducted in various regions of Ethiopia [ 25 , [31] , [32] , [33] , [34] , [35] , 62 , 66 , 67 ], the SIT149/T3-ETH sub-lineage, which has been found to be more likely in a cluster [ 13 , 20 , 65 ], was the most common in our study, followed by the SIT52/T2 spoligotype. In the current study region, SIT149/T3-ETH sublineage [ 39 ] was reported as a predominant TB strain.…”
Section: Discussionsupporting
confidence: 92%
“…The genetic diversity and geographic distribution of MTB lineages have been studied across different settings and regions of Ethiopia [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] and revealed the presence of diverse MTBC sublineages. The Ethiopian-specific lineage (SIT149/T3-ETH sublineages) was reported as a predominant TB strain in the country [ 25 , [31] , [32] , [33] , [34] , [35] ], while lineage 3/CAS1-DELHI sublineages was another widespread strain in certain regions of Ethiopia [ 20 , 26 , 27 , 36 ]. In the current study region, lineage 3/CAS1-DELHI [ 20 , 21 , 37 , 38 ], and lineage 4/T3-ETH sublineages [ 39 ] were identified as the most abundant TB strains.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively large cluster (n = 11) of the SIT41 spoligotype, which is phylogeographically specific to Turkey [ 44 ], was reported in this study with the majority (10/11) being from patients in southeastern (Borena and Guji) Ethiopia. This sub-lineage, although in small numbers (n ≤ 5), was previously reported [ 23 , 28 , 30 , 32 , 43 , [45] , [46] , [47] , [48] ] in different parts of Ethiopia. Similarly, it was reported to be less common in the African continent [ 49 ].…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with other investigations carried out in Ethiopia [ [11] , [12] , [13] ], the T3-ETH sub-lineage/SIT149 spoligotype, reported to be more likely in a cluster [ 36 , 41 , 42 ], was the most frequent in our study, followed by the T1 sub-lineage/SIT53 spoligotype. A study conducted in Oromia region [ 43 ], which included the zones from which two-thirds of our isolates were obtained, found a high proportion of clustered ST149 spoligotype followed by orphan spoligotypes rather than the commonly reported T or CAS sub-lineages. This could be attributed to several factors including differences in sampling techniques, the broad geographic area and high population of the region and the relatively small sample size used in the current study.…”
Section: Discussionmentioning
confidence: 86%